2017
DOI: 10.1111/gcb.13679
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐dependent complementarity of climatic velocity and environmental diversity for identifying priority areas for conservation under climate change

Abstract: As most regions of the earth transition to altered climatic conditions, new methods are needed to identify refugia and other areas whose conservation would facilitate persistence of biodiversity under climate change. We compared several common approaches to conservation planning focused on climate resilience over a broad range of ecological settings across North America and evaluated how commonalities in the priority areas identified by different methods varied with regional context and spatial scale. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
179
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 122 publications
(180 citation statements)
references
References 57 publications
0
179
1
Order By: Relevance
“…(I) Mean climate refugial index; ranges from 0 to 3.29 in contiguous United States, larger values indicate greater refugial potential (source: Carroll et al. ). (J) Mean LCV score (percentage of pro‐environment votes on environmental legislation) for eight years prior to designation (source: League of Conservation Voters, LCV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(I) Mean climate refugial index; ranges from 0 to 3.29 in contiguous United States, larger values indicate greater refugial potential (source: Carroll et al. ). (J) Mean LCV score (percentage of pro‐environment votes on environmental legislation) for eight years prior to designation (source: League of Conservation Voters, LCV).…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated the capacity for PAs to support future biodiversity using an index of climate refugial potential (Carroll et al. ) derived from backward climate velocity (BCV), the rate of movement required for an organism adapted to a location's predicted future climate to reach that location. Areas with lower BCV should be more easily colonized by organisms shifting their distribution to remain within suitable climatic conditions and thus should have greater potential to serve as climate refugia (Carroll et al.…”
Section: Methodsmentioning
confidence: 99%
“…However, we found that climate connectivity priorities were robust to uncertainty caused by variation in input data between alternative emission pathways (RCP 4.5 and 8.5) and AOGCMs. Priorities based on centrality derived from different AOGCMs showed less between‐AOGCM variation than did the input climate data or climatic velocity metrics based on that climate data (Carroll et al, ). Conservation planners may place greater focus on sensitivity analyses of the effect of assumptions concerning dispersal behavior and analysis extent, rather than on parameter uncertainty arising from differing climate projections.…”
Section: Discussionmentioning
confidence: 99%
“…There exists much uncertainty over how to identify refugia within landscapes to target management spatially (Ashcroft, 2010). Putative refugia (micro-and macrorefugia) are typically located using simple heuristics, most commonly that areas with high topographic heterogeneity are likely to function as refugia (Ashcroft, 2010;Carroll et al, 2017;Dobrowski, 2011). There is less guidance about identifying refugia in areas of modest terrain (Reside et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing interest in developing fine-scale grids of micro-or topo-climate, often with ~30 m pixels, via downscaling techniques Dingman et al, 2013;McCullough et al, 2016) or interpolation from dense sensor arrays (Ashcroft, 2010;Frey et al, 2016) to identify microrefugia. An important source of uncertainty is that different measures and different methodological choices identify different sites as candidate refugia (Ashcroft, 2010;Ashcroft et al, 2012;Carroll et al, 2015Carroll et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%